REKONSTRUKSI PEMAHAMAN HADIS GHADIR KHUM - noorhidayati, salamah (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
Hadith ghadir khum is the culmination of a dispute between Sunni and Shi?ite. This article tries to analysis comprehensively the hadith by elaborating understanding in two perspectives: exploring the factors that cause these differences and re-understandinging the interpretation hadith. This study found that there were differences in understanding between the Sunni and Shi?ite schools in understanding the hadith. This difference is at least caused by two things, namely: the context of the hadith and the meaning of the word maul. According to the Sunnis, this hadith contains a warning from the Prophet to his people to love and help one another (having walâ?- muwalât) and not hating and opposing each other (mu?âdat). Meanwhile, according to Shi?ah, this hadith is considered a moment in which the Prophet directly named Ali as a successor and successor to the leadership after the Prophet. Reconstruction of understanding is done through two things, namely the historical reconstruction and reinterpretation of the meaning of the womb. Overall, the ghadir khum hadith is interpreted as a form of the Prophet?s love for the people and their families. The love of his people is proven by his will in the form of thaqalain, namely al-Kitab (Alquran) and love for his family with the intention to make Ali (representation of ahl al-bait) as maulâ (friend, lover) of Muslims.